PENGADAAN BARANG / JASA DAN PELAKSANAAN KONSTRUKSI PENINGKATAN KAPASITAS JALAN TOL PALIMANAN - KANCI - , SHOFA SYAHIDI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traffic in highway keep increase so it is necessary to increase capacity, it is intended to drive swiftly, secure and comfortable accordance with PT. Jasa Marga vision and mission âgive quality services in a optimal toll road to road usersâ. Increase capacity work includes the procurement of goods / services and and physical work. Realization lane add at Km 222+550 to 223+000 track A on Palimanan â Kanci highway. The purpose of this research is know the scope of procurement activities and construction work on the capacity building of segment toll booths Cipema Utama. The method used is the method of observation is by direct observation of the implementation of the field work, literature study is a way to use some of the literature related to content writing reports reinforce, documentation is to take some photos of observation, interview method is to ask the stakeholders involved directly and also responsible for the technical problems in the field. The conclusion that can be drawn is the procurement of services electoral system uses pre-qualification, method 2 cover and use the evaluation system value. Construction using flexible pavement construction (flexible pavement). Work being tested (trialtest) is setting traffic signs, and pavement testing consists of, scrapping, filing, and core drill.